COLLABORATE BETWEEN DIGITAL PLATFORM AND STUDENTS’ CREATIVITY IN LEARNING DURING COVID-19 - Helsa Gita Almaida; Dewi Suriyani Djamdjuri (LPPM UIKA Bogor, 2021)
The impact of the COVID-19 pandemic can change psychological conditions and change human life, especially in human activities for a long time. Besides, the COVID-19 pandemic is affecting the education system in Indonesia, where the educational process usually changes with a distance learning process using technology. With a structured learning process, you can learn knowledge and skills using technology. Thus the learning method is following collaborating between digital platforms, and student creativity in learning. Therefore this study aims at students who are creative, effective, and think critically in the online learning process. Data were collected using interviews and observations. The results showed that there was a significant influence on students' creativity, active, and critical thinking in collaborative digital platforms.